Increasing efficiency of radiant heating systems’ work - Shepitchak, Volodymyr; Zhelyh, Vasyl (Видавництво Львівської політехніки, 2013)
The possibility of the application of energy efficient heating systems based on infrared light for heating industrial premises has been analyzed in the article. The experimental studies of temperature condition exposure zone of the rotary infrared heaters. The rotary radiation heater represents the distribution of the exposure intensity depending on the height disposition. The results are presented in graphical interpretation.
Keywords: heat; energy-efficient systems; heating; infrared heaters; radiant energy